Assistência às mulheres soropositivas (HIV/AIDS) na Atenção Básica no município de Itabaiana (SE) - Santos, Maria Edilma de Jesus (2022)
It is understood that women with HIV/AIDS have presented situations of vulnerability and specific needs that are not always recognized and satisfied by services aimed at assisting HIV/AIDS people. These situations are permeated by unequal relations of gender and power that point to the need for studies and intervention on the gender approach, particularly women with HIV/AIDS. The main goal of this research is to analyze and identify the relationship between the feminization of HIV/AIDS and its interface with gender inequalities in HIVpositive women assisted in Primary Care in the city of Itabaiana/SE. Dialectical historical materialism offers epistemological and ontological elements for understanding the totality of the object of this research in capitalist society, establishing a relationship with the determinations of reality. The feminist approach is pertinent, as it is an investigation within the scope of gender studies, prioritizing the discovery of themes, categories and concepts, based on the phenomenon's data, the work of this researcher and her worldview, as a primary tool for understanding the object. The qualitative methodology is based on documentary sources and bibliographies such as: a) consultation of the Bank of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES) with the 2014- 2020 time frame, to map the production of the knowledge about the object in the field of Social Work; b) ) data made available by the Ministry of Health related to the medical records of the Health Department of Itabaiana/SE on the care of seropositive women, prioritizing the Primary Care of the Municipality in the indicated time frame. The bibliographical review, whose theoretical basis is found in classic and contemporary scientific books and articles, will take place in the methodological process, in the approach to the theme, in the interlocution of theory and data, based on qualitative analyzes and documentary sources. Health inequalities – in health conditions or in health services – are not a 'fact of nature'. The rectification of these inequalities, in the present and in the past, has always involved confronting social injustices. To achieve equity in health, the main focus of health and public health services must be equity in health – not just achieving an average standard of health. Differences in the field of health are inscribed in a set of social relationships (determined by historical and social formation), which, based on the lived experience of each subject, create a subjectivity and an identity. Differences between race, class, gender, generation and sexuality are placed as axes of differentiation or markers of difference. We consider it essential that health professionals start to consider the “interrelationships of the various forms of social, empirical and historical differentiation, but without necessarily deriving all of them from a single determining instance”.